A 3D Multi-scale geology modeling method for tunnel engineering risk assessment. (March 2018) - Xiong, Ziming; Guo, Jiateng; Xia, Yuanpu; Lu, Hao; Wang, Mingyang; Shi, Shaoshuai
Highlights: Proposed a modeling method of regional scale geological 3D model using the Hermite radial basis function for preliminary evaluation. Put forward a project scale geological modeling method for pre-evaluation, which was based on coupling of geological body model of surrounding rock and tunnel model, with updating, refining and expanding the regional scale geological 3D model by the dense drilling data and geological prediction data. Presented a outcrop scale geological modeling method using Monte-Carlo algorithm for dynamic evaluation. Abstract: A method for 3D multi-scale geology modeling is proposed for assessing tunnel engineering risk. Risk assessments have varying requirements at various different construction stages, therefore the proposed model can be modified for different scales. The regional scale 3D geological model, based on regional field surveys of geological boundary and attitude, is proposed for conducting preliminary evaluations with limited geological sampling data and the Hermite radial basis function (HRBF). The project scale geological model, based on updating and refining the regional scale model with dense drilling and geological prediction data, couples the geological body model for surrounding rock and the tunnel model. This project scale model is appropriate for performing pre-evaluations of tunnel construction. Once construction has begun, continuous rock structure surface information from the newly exposed tunnel face is incorporated into the outcrop scale geological model. It is based on a Monte-Carlo algorithm for conducting dynamic evaluations during construction. These modeling methods are applied to a case study, railway tunnel engineering of the Yuelongmen tunnel in China.